Studi Cross-Sectional Tentang Pengetahuan, Sikap, dan Praktik Terhadap Penggunaan Obat OTC Di Kalangan Mahasiswa Farmasi Universitas Muhammadiyah Riau - Nursyafni; Nurbaiti; Reza laila Najmi; Rahmi Amini; Izza Aulia Risqika Nasution; Lilian Rahma Dayani; Najmi Hilaliyati (The Journal Of Pharmacy, 2024)
OTC (Over the Counter) drugs are a class of over-the-counter and limited over-the-counter drugs, which can be purchased without a prescription from a doctor, are safe, and effective when used according to the instructions on the drug packaging label. This study is a cross-sectional study that aims to evaluate the knowledge, attitudes, and practices towards the use of OTC drugs among Pharmacy students of the University of Muhammadiyah Riau. The study sample consisted of 86 respondents, consisting of 86% female and 14% male, with the majority aged 19-21 years. Data were collected using a validated questionnaire and analyzed using the Spearman correlation test to determine the relationship between knowledge, attitudes, and practices. The results showed that 62.8% of respondents had sufficient knowledge about OTC drugs, 64% had moderate attitudes, and 79.1% showed positive practices in the use of OTC drugs. Correlation analysis showed a significant positive relationship between knowledge and attitude (correlation coefficient: 0.362; p=0.001), knowledge and practice (correlation coefficient: 0.751; p=0.000), and attitude and practice (correlation coefficient: 0.553; p=0.000). These findings indicate that increasing knowledge about OTC drugs can contribute to more positive attitudes and better practices in their use. This study provides important insights for educational institutions in designing more effective educational programs to improve pharmacy students' knowledge, attitudes, and practices towards OTC drugs. Increased knowledge is expected to not only shape more positive attitudes, but also encourage safer and more responsible drug use practices